Characterization of the meta-Cleavage Compound Hydrolase Gene Involved in Degradation of the Lignin-Related Biphenyl Structure by Sphingomonas paucimobilis SYK-6 - Peng, Xue (American Society for Microbiology, 1999)
Sphingomonas paucimobilis SYK-6 has the ability to transform a lignin-related biphenyl compound, 2,2′-dihydroxy-3,3′-dimethoxy-5,5′-dicarboxybiphenyl (DDVA), to 5-carboxyvanillic acid (5CVA) via 2,2′,3-trihydroxy-3′-methoxy-5,5′-dicarboxybiphenyl (OH-DDVA). In the 4.9-kb HindIII fragment containing the OH-DDVA meta-cleavage dioxygenase gene (ligZ), we found a novel hydrolase gene (ligY) responsible for the conversion of the meta-cleavage compound of OH-DDVA to 5CVA. Incorporation of (18)O from H(2)(18)O into 5CVA indicated there was a hydrolytic conversion of the OH-DDVA meta-cleavage compound to 5CVA. LigY exhibited hydrolase activity only toward the meta-cleavage compound of OH-DDVA, suggesting its restricted substrate specificity.